PEMAHAMAN DIGITAL DAN IMPLEMENTASI QRIS BANK SYARIAH INDONESIA PADA PEDAGANG UMKM KULINER DI KECAMATAN TELANAIPURA KOTA JAMBI - Salma Mauliyanti; Ambok Pangiuk; Faturahman Faturahman (Yayasan Nusantara Hasana Berdikari, 2026)
This study is motivated by the development of digital technology in non-cash payment systems through the Quick Response Code Indonesian Standard (QRIS), particularly at Bank Syariah Indonesia (BSI). Although the use of BSI QRIS among culinary MSME merchants in Telanaipura District, Jambi City is relatively high quantitatively, the digital understanding of business actors remains low and its implementation is not yet optimal. This condition indicates a gap between the level of usage and the quality of QRIS utilization in supporting more efficient, transparent, and professional business management. This study aims to determine the level of digital understanding of culinary MSME merchants regarding the use of BSI QRIS, analyze its implementation in daily business activities, and identify the efforts made by Bank Syariah Indonesia to improve understanding and optimize the use of BSI QRIS. The research method used is a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation of culinary MSME merchants located on Arif Rahman Hakim Street, Telanaipura District, Jambi City. Data analysis techniques include data reduction, data presentation, and conclusion drawing, while data validity is ensured through triangulation. The results show that the digital understanding of MSME merchants regarding BSI QRIS is still relatively low and uneven. Most merchants use QRIS only as a non-cash payment tool without fully understanding its functions, benefits, and operational mechanisms. The implementation of BSI QRIS in business activities is still administrative and formal in nature, and has not been optimally utilized for transaction recording and financial management. The efforts made by Bank Syariah Indonesia (BSI) include socialization and education, assistance and facilitation, as well as monitoring and evaluation, which have improved digital understanding and encouraged QRIS adoption; however, their implementation is not yet fully optimal due to uneven distribution and limited follow-up on evaluation results.